Fibromioma Extra-Peritoneal do Ligamento Redondo. Caso Clínico - Carocha, A (2015)
Fibromyoma of the round ligament should be considered as a possible etiology for a large preperitoneal tumor. We report a case of a 44-year-old female who was found to have a fibroleiomyoma that measured 14 cm, weighed 3599 gr and had grown in the abdominal wall between the muscle and the peritoneum, taking as its starting point the right round ligament.